The use of the project portal: an analysis of the satisfaction perception of users in an university in Rio Grande do Sul State, Brazil (Research, Society and Development, 2020)
A survey sought to identify the level of satisfaction of users of the UFSM project portal. For applied data collection, a survey is conducted through a structured questionnaire with 68 closed questions. How much is the data analysis applied to four techniques, namely: descriptive analysis, exploratory factor analysis, Test and ANOVA with Post Hoc. The results that most participants do not experience difficulties interacting with the project portal, claim to be able to use the system, consider it useful in their professional activities, which allow the execution of tasks more quickly than when they used it in the previous system, which improved the project registration process in relation to the old system, and presents a level of detail sufficient for your needs. It is noticed that, in general, the items with the greatest difficulty highlighted by the participants are issues related to the budget, goals, indicators. To obtain results, it is possible to highlight the need for some improvements to make the platform more intuitive, to develop a tutorial with information on filling in financial data, mainly, phases, goals and indicators and to conduct training and qualification for users.